Strategic Synthesis and Supramolecular Organization of Arylenebis(aryliodonium) Salts; Journal of Organic Chemistry; Vol. 90, iss.44 - Knyazeva E. V. Elizaveta Vyacheslavovna; Soldatova N. S. Nataliya Sergeevna; Abramov P. A. Pavel Aleksandrovich; Ivanov D. M. Daniil Mikhaylovich; Burykina Ju. V. Julia; Radzhabov A. D. Amirbek Dzhurabekovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Resnati D. P. Dzhuzeppe Paolo; Kukushkin V. Yu. Vadim Yurjevich; Postnikov P. S. Pavel Sergeevich (2025, 2025)
Title screen